The Attitudes of the Faculty Members At Al-Balqa' Applied University Towards the Application of E-Learning in University Teaching from their Own Perspective - Mohammad Al- Hawamdeh (My University, 2010)
The purpose of this study was to examine the attitudes of the faculty members at Al-Balqa' Applied University towards the application of electronic learning (E-learning) in university teaching as well as to investigate the impact of three main variables on these attitudes. Those variables were: attending training courses in the field of E-Learning, gender, and years of experience. In order to attain these two main objectives, a questionnaire consisting of (20) items was developed and distributed to a sample of (81) faculty members teaching at Irbid University College. The results of the study indicated that the attitudes of faculty members at Al-Balqa' Applied University towards the application of E-learning were positive in general. Moreover, the results of the study showed statistically significant differences among the attitudes of faculty members at Al-Balqa' Applied University towards the application of E-learning. These differences were attributed to the variable of attending training courses in field of E-Learning and in favor of attending 'More Training Courses' category. On the other hand, neither the gender variable nor the years of experience variable resulted in any statistically significant differences among the faculty members' attitudes towards the application of E-learning. In light of the findings of the current study, a number of recommendations were made.

هدفت هذه الدِّراسة إلى الكشف عن اتجاهات أعضاء الهيئة التدريسيّة في جامعة البلقاء التطبيقيّة نحو استخدام التعلّم الإلكترونيّ في التدريس الجامعيّ من وجهة نظرهم، وتعرّف أثر الحصول على الدورات التدريبيّة في مجال الحاسوب والتعلم الإلكترونيّ، ومتغير الجنس، ومتغير سنوات الخبرة في التدريس، في هذه الاتجاهات. ولتحقيق ذلك تمّ تطوير (مقياس الاتجاهات) المكون من (20) فقرة بعد التحقق من صدقه وثباته، وقد تمّ توزيعه على عينة الدِّراسة المكونة من (81) عضواً من أعضاء الهيئة التدريسيّة في كلية إربد الجامعيّة. وبعد أن تمّ إجراء التحليلات الإحصائيّة المناسبة، أظهرت نتائج الدِّراسة أن اتجاهات أعضاء الهيئة التدريسيّة في جامعة البلقاء التطبيقيّة نحو استخدام التعلّم الإلكترونيّ على المقياس ككلّ بأنها إيجابيّة، وأظهرت نتائج الدِّراسة وجود فروق ذات دلالة إحصائيّة في اتجاهات أعضاء الهيئة التدريسيّة في جامعة البلقاء التطبيقيّة نحو استخدام التعلّم الإلكترونيّ، تعزى لأثر متغير الحصول على الدورات التدريبيّة في مجال الحاسوب والتعلم الإلكترونيّ، ولصالح من حضروا "ثلاث دورات تدريبية فأكثر". كما أظهرت النتائج أنه لا توجد فروق ذات دلالة إحصائيّة في اتجاهات أعضاء الهيئة التدريسيّة نحو استخدام التعلّم الإلكترونيّ تعزى لأثر الجنس، أو لأثر سنوات الخبرة في التدريس، وفي ضوء نتائج الدِّراسة قدَّم الباحث مجموعة من التوصيات.
اتجاهات أعضاء الهيئة التدريسيّة في جامعة البلقاء التطبيقية نحو استخدام التعلّم الإلكترونيّ في التدريس الجامعيّ من وجهة نظرهم